Fortalecimiento de las microempresas comerciales de alimentos cárnicos en la zona Eloy Alfaro del Sur de Quito, en el marco de la economía popular y solidaria, para afrontar la crisis económica del país - Campo Calahorrano, Jenny Patricia (2017)
Strengthening of the commercial micro-enterprises of meat products in the Eloy Alfaro, South Zone of Quito, within the framework of the Popular and Solidarity Economy, to confront the country's economic crisis. Microenterprises are economic units of fundamental importance in the socioeconomic situation of the country, because of their capacity to generate value and employment, so that any research that focuses on improving and strengthening them is considered a valuable contribution. This research has been developed in order to analyze the environment in which the commercial microenterprises of food of the Zone Eloy Alfaro of the South of Quito operate, and to recommend actions for its strengthening in the framework of the Popular and Solidary Economy. Its development has included first tackling the problem, then it has become aware of the Popular and Solidarity Economy (EPS), determining that this economic model seeks to generate a more just and equitable society; the microenterprises that are the subject of study have been analyzed, and it is possible to strengthen them by means of associativity, as a strategy to improve their income, profitability, access to new markets, facilitate financing and contribute to the development of country. Finally, it is recommended to socialize the results of the research, especially regarding the associative strategy, for the benefits that can generate.